A Retrospective Reflection on the Life History and the Philanthropic Attitude of Bharat Ratna Dr.Marudhur Gopala Menon Ramachandran a A Birdas Eye View (Global Journal of Human-Social Science, 2018)
The nobleness and philanthropic attitude of Bharat Ratna Marudhur Gopala Menon Ramachandran Dr MGR is known to the people of Tamil Nadu and the Tamils all over the world In this research paper the nobleness of Dr MGR is illustrated with few of the real life experience of Dr MGR that will enlighten the noble quality of Bharat Ratna Dr Marudhur Gopala Menon Ramachandran This research work traces the history of Dr MGR primarily and thereafter the noble deeds performed by him are dealt in detail In the end the various welfare measures implemented by him as the Chief Minister of Tamil Nadu are enlisted in order to make a heuristic study of the research work The contents of this paper is part of the research work carried out by me entitled as Equity and Social Justice Economic and Social Welfare Ideas Emphasized in Bharat Ratna Dr M G Ramachandran s Film Songs in Comparison with Contemporary Theories